Do bank insiders impede equity issuances? - Goetz, Martin R.; Laeven, Luc; Levine, Ross (Journal of Financial Intermediation, 2025)
We construct a novel panel of insider ownership for roughly 600 U.S. bank holding companies from 2003 to 2014 to test whether ownership structure shaped recapitalizations around the Global Financial Crisis (GFC). Insider ownership shows no discrete shift around the GFC. Using a difference-in-differences design with BHC and time fixed effects, we find that, after Q3 2008, banks with higher pre-crisis insider stakes issued significantly less common equity than otherwise similar peers. This effect is more pronounced where insiders enjoy greater private benefits of control, as proxied by insider lending and earnings opacity—consistent with dilution reluctance as the mechanism. The findings hold in propensity score matched regressions and when employing instrumental variables for insider ownership. These results reveal that ownership structure affects banks’ equity issuances in crises, underscoring the importance of accounting for ownership structure in bank stress tests and capital-regulation frameworks.